Statistical estimation of random failure probability based on stress levels. (14th June 2022) - Sim, Hyun Su; Jung, Jin Hyeong; Kim, Yong Soo
We develop a new method for estimation of random failure probability; this will inform test design and statistical analysis. First, the random failure mechanism is characterised so that a suitable test can be designed. Second, the experimental results are statistically analysed. This enables the development of a Gompertz model of the failure characteristics, which are then extrapolated, and the failure probability is estimated. The probability of random brake disc failure in the real world was quantitatively estimated using a case study: a reliability test of random failure caused by hot judder designed by a user based on our model.